Broad size interval monodisperse mesoporous phenolic carbon spheres, controllable preparation method and application thereof
Patent Information
- Application Number
- CN202611396641.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-30
AI Technical Summary
3. 氨水催化存在奥斯特瓦尔德熟化现象,添加量达到一定值后 颗粒融合变大,仅单一的组分(比如:氨水量;酚醛比例;模板剂量;乙醇和水比例;温度等)无法实现 200~1000 nm 线性连续调控;
1. 拓宽原料与模板保护范围,本发明方法全部采用实验室 或工业化成熟通用试剂,软模板覆盖阳离子、非离子、阴离子表面活性剂,硬模板细化三类硅源(烷氧基硅烷、硅溶胶、气相白炭黑),同时兼容苯酚、间苯二酚;中等极性,所有软模板和硅硬模板均可稳定组装。通过苯酚或间苯二酚+软模板 + 硅烷/硅溶胶系列硬模板 + 固定 1:1 醇水溶剂 +25~30℃恒温 + 氨水控制在熟化拐点前 + 双变量协同线性控粒径整套约束组合,可同时实现宽尺寸、高球形度、稳定介孔。
Smart Images

Figure CN123002819A_ABST
Abstract
Description
Technical Field
[0001] This invention pertains to the synthesis technology of porous functional carbon materials, specifically involving a standardized and controllable preparation process for a universal soft and hard template-type phenolic resin precursor and mesoporous carbon spheres with a wide size range. Background Technology
[0002] Spherical mesoporous carbon, with its uniform particle size, controllable pores, and high specific surface area, possesses irreplaceable application value in electrochemical energy storage, wastewater treatment, gas separation, and catalyst supports. Currently, the mainstream preparation routes mainly involve phenolic monomers, aldehyde crosslinking agents, template agents, ammonia catalysis, and alcohol-water solvent polymerization; however, existing technologies have several limitations: 1. Limited template materials and narrow protection scope: Most patents only limit the use of CTAB as a single soft template and do not include industry-standard F127, PVP, and SDS; hard templates only vaguely mention silicon dioxide and do not specify mature silicon sources such as TEOS, TPOS, TMOS, and silica sol, which cannot cover different pore size control needs; at the same time, only resorcinol is used and it is not compatible with low-cost phenol monomers. 2. Particle size control depends on solvent change and temperature adjustment: High water ratio solvents are too polar, causing cationic soft template micelles to dissociate, resulting in flocculent and random products; high ethanol system prepolymers rapidly aggregate, resulting in extremely wide particle size distribution; temperature increase destroys the orderly assembly of the template, causing a large number of mesopores to collapse and a sharp drop in specific surface area; 3. Ammonia catalysis exhibits Ostwald ripening, where particle size increases after a certain addition amount. A single component (e.g., ammonia amount; phenolic ratio; template dosage; ethanol and water ratio; temperature, etc.) cannot achieve linear and continuous control of the particle size from 200 to 1000 nm. 4. The process variables are heavily coupled, there is no standardized scheme for fixed alcohol-water + constant temperature, and batch repeatability is poor.
[0003] For example, CN119683620A can only prepare millimeter-sized spheres and cannot reach the 200~1000 nm submicron range; CN11830773B is a suspended millimeter sphere, which is completely out of scale. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings of existing technologies by providing a wide-size-range monodisperse mesoporous phenolic carbon sphere and a multi-template controllable preparation method thereof, so as to obtain phenolic carbon spheres with a wide size range, high sphericity, and stable mesoporous structure, and to achieve linear and continuous control of particle size from 200 to 1000 nm.
[0005] The present invention provides a room-temperature controllable preparation method for monodisperse mesoporous phenolic carbon spheres with a wide size range, comprising the following steps: Step 1: Dissolve or uniformly disperse the soft template in a mixed solvent with an ethanol to water volume ratio of 1:1 at a constant temperature of 25~35℃; or pre-hydrolyze the silicon source hard template in water at a constant temperature of 25~35℃, then add ethanol at a volume ratio of 1:1 and maintain a constant temperature. Then, add 25-28 wt% ammonia catalyst and stir until homogeneous. The volume of ammonia should be 3.0-5.0 vol% of the volume of the ethanol and water mixture to obtain the reaction mixture.
[0006] Step 2: Maintain a constant temperature and add phenol and formaldehyde aqueous solution to the obtained reaction mixture. The molar ratio of phenol to formaldehyde in the aqueous solution is 1:(2~3). Stir at a constant temperature for 18~24 h to carry out the polymerization reaction. The phenol is phenol and / or resorcinol, and the mass concentration of the formaldehyde aqueous solution is 37%. After the reaction is completed, the solid and liquid are separated, and the mixture is washed alternately with ethanol and water. Then, it is vacuum dried at 40~60 °C to obtain the resin precursor. Step 3: Perform template removal treatment on the obtained resin precursor: the soft template is decomposed by carbonization; the silicon source hard template is removed by acid etching or alkaline etching after carbonization. The carbonization and decomposition method is as follows: under a nitrogen and / or argon atmosphere, the temperature is increased to 800℃ at 5℃ / min and held for 2 hours for carbonization, and then cooled to obtain mesoporous phenolic carbon balls.
[0007] The acid etching or alkaline etching method is as follows: After carbonization according to the above method, the desilication template is soaked in 5~10% hydrofluoric acid or hot concentrated NaOH of the total mass of carbonization to obtain carbon balls.
[0008] Step 4: When using a silicon-based hard template, after acid etching or alkaline etching, carbonize the material by heating it to 750–850 ℃ at a rate of 4–6 ℃ / min under an inert atmosphere of nitrogen or argon, holding it at that temperature for 1.5–2.5 h, and then cooling it to obtain mesoporous phenolic carbon spheres.
[0009] The above method maintains the same solvent and temperature range throughout the process. By simultaneously adjusting the amount of template and ammonia added, and keeping other conditions constant, the average particle size of the resin microspheres can be continuously and linearly controlled within the range of 200 nm to 1000 nm. Increasing the amount of template and ammonia simultaneously reduces the particle size of the prepared mesoporous phenolic carbon spheres; conversely, decreasing the amount of template and ammonia simultaneously increases the particle size, achieving a linear and continuous change within a wide size range of 200–1000 nm.
[0010] In the above method, the temperature of the mixed solvent in step 1 is preferably constant at 30°C to eliminate the damage of temperature to micelles, cross-linked networks, and pores.
[0011] In the above method, the volume ratio of ammonia catalyst in step 1 is always below the 5.5 vol% particle size reversal inflection point. The volume of ammonia water accounts for 3.0~5.0 vol% of the volume of the mixed solvent of ethanol and water. This parameter range was determined through experimentation. Ammonia water in this system has a dual role as a polymerization catalyst and a regulator of micelle surface charge; when the volume fraction of ammonia water exceeds 5.5 vol%, the system becomes too alkaline, which will significantly exacerbate the Ostwald ripening effect, resulting in a particle size reversal phenomenon where small resin particles dissolve and then undergo secondary deposition and growth on the surface of large particles. The design concept of controlling ammonia water at 3.0~5.0 vol% and below the 5.5 vol% inflection point is to: provide sufficient alkalinity to ensure the normal addition-condensation polymerization reaction of the phenol-formaldehyde system, while maintaining sufficient electrostatic repulsion between particles to inhibit random agglomeration; more importantly, to avoid the ripening inflection point, ensuring that, under the condition of simultaneously adjusting the amount of template agent and ammonia water added, the particle size decreases monotonically with the increase of template and ammonia water dosage. Without this limitation, if the ammonia content exceeds 5.5 vol%, a large number of irregularly shaped particles will fuse together, the particle size distribution will widen sharply, and the linear adjustable particle size will be lost, making it impossible to obtain the 200 nm to 1000 nm monodisperse spherical phenolic resin microspheres required by this invention.
[0012] In the above method, the soft template is selected from at least one of the following: cationic CTAB (hexadecyltrimethylammonium bromide) and CTAC (hexadecyltrimethylammonium chloride); nonionic F127 (poloxamer F127) and PVP (polyvinylpyrrolidone) (products prepared under this type of template have large mesopores and slightly wider particle size distribution); and anionic SDS (sodium dodecyl sulfate) (this type of template easily forms flakes and is only used as an auxiliary compound).
[0013] When the aforementioned soft template, SDS anionic template, is used alone, the phenol-aldehyde polymerization system easily generates plate-like random products, making it difficult to obtain regular spherical microspheres. Therefore, SDS is best not used alone, but only as an auxiliary component, compounded with cationic soft templates CTAB or CTAC, to fine-tune the micelle structure of the system and slightly widen the mesopore size of the product. There is an optimal mass ratio range for the compounded components: the preferred mass ratio of SDS to cationic soft templates (CTAB or CTAC) is 1:(3-4). The compounded components exhibit a significant synergistic effect: cationic CTAB or CTAC constructs a basic regular micelle framework in the system, ensuring that phenol-aldehyde polymerization preferentially generates spherical resin particles, fundamentally avoiding the plate-like random products generated when SDS is used alone; a small number of anionic SDS molecules insert into the micelle shell layer of the cationic micelles, changing the surface charge density and packing arrangement of the micelles, moderately perturbing the micelle aggregation structure, and achieving a slight widening of the mesopore size while maintaining the high sphericity and monodispersity of the microspheres. If the SDS content is too high (SDS: cationic template mass ratio > 1:2), the anionic and cationic surfactants in the system are prone to undergo a large amount of ion pair complexation precipitation, the micelle structure is destroyed, and plate-like and irregularly shaped resin products reappear. If the SDS content is too low (SDS: cationic template mass ratio < 1:5), the perturbation effect of SDS on micelles is weak, and the pore size broadening effect is almost unobservable, making the compounding meaningless for practical control. The innovation of this compounding strategy is that it does not require changing the template type or modifying the solvent and temperature conditions. By compounding a small amount of anionic-cationic template, the mesopore size of carbon spheres can be finely adjusted within the fixed 1:1 ethanol-water, isothermal polymerization system of this invention, enriching the adjustable pore size window without changing the entire particle size control process.
[0014] In the above method, the soft template is preferably one of CTAB or CTAC, which provides optimal monodispersity of the microspheres. When using these soft templates, after in-situ carbonization to remove the template, the phenolic carbon spheres obtained have a pore size of approximately 2.0 nm.
[0015] In the above method, the amount of soft template added is equal to the mass of the ethanol and water mixed solvent in step 1. 0.20~0.50 wt%; removed by direct thermal decomposition during the carbonization stage, without the need for acid or alkali etching.
[0016] In the above method, the hard template is selected from one of alkoxysilane, neutral nano-silica sol, alkaline nano-silica sol, and fumed silica. The alkoxysilane is selected from at least one of TEOS (tetraethyl orthosilicate), TPOS (tetrapropoxysilane), and TMOS (tetramethoxysilane). Before adding the alkoxysilane in step 1, it is pre-hydrolyzed for 10-30 min to generate nano-SiO2 precursor; the nano-silica sol is a 5-50 nm monodisperse SiO2 colloid, which is directly dispersed in step 1 without hydrolysis.
[0017] In the above method, the amount of hard template added is 0.15~0.60 wt% of the mass of the ethanol and water mixed solvent in step 1; In the above method, the preferred amount of soft template added in step 1 is 0.20~0.50 wt% CTAB: when preparing phenolic carbon balls with a particle size of 200 nm, 0.50 wt% CTAB is combined with 5.0 vol% ammonia water; when preparing phenolic carbon balls with a particle size of 1000 nm, 0.20 wt% CTAB is combined with 3.0 vol% ammonia water.
[0018] In the above method, the preferred hard template in step 1 is TEOS or TPOS, the preferred amount added is 0.2~0.5 wt%, and the preferred pre-hydrolysis time is 20 min.
[0019] In the above method, the molar ratio of phenol to formaldehyde is preferably 1:2.5.
[0020] In the above method, step 3, acid etching, is performed by immersing the sample in hydrofluoric acid with a mass concentration of 10-20% for 6-24 hours; the acid etching method is performed by immersing the sample in an aqueous solution of NaOH with a mass concentration of 5-10% at a temperature of 60-90°C for 3-6 hours.
[0021] The present invention also provides monodisperse mesoporous phenolic carbon spheres prepared by the above method, wherein the carbon sphere particle size is continuously adjustable from 200 to 1000 nm and the sphericity is ≥95%; when using a soft template, the average pore size of the carbon is 2.2 to 3.1 nm, and when using a silicon-based hard template, the average pore size of the carbon after desilication is 4.5 to 5.2 nm; the BET specific surface area is 600 to 1490 m² / g.
[0022] This invention also provides applications of the above-mentioned monodisperse mesoporous phenolic carbon spheres in the fields of supercapacitor electrode materials, adsorption treatment of organic pollutants in industrial wastewater, multiphase catalytic reaction carriers, and gas separation chromatography packing materials. The monodisperse mesoporous phenolic carbon spheres prepared by this invention have a controllable and tunable particle size of 200–1000 nm, are perfectly spherical, and have a narrow particle size distribution, while possessing a stable small mesoporous channel structure and a high specific surface area. When used as supercapacitor electrodes, the uniform spherical particles are beneficial for constructing a stable conductive network and alleviating volume stress during charging and discharging. When used for wastewater adsorption, the regular mesoporous structure is beneficial for the mass transfer and diffusion of organic pollutants. As a multiphase catalytic carrier, the monodisperse spherical morphology can reduce catalyst agglomeration and facilitate uniform loading of active components. As a chromatographic packing material, the narrowly distributed spherical particles can improve the uniformity of column bed packing and reduce the mass transfer resistance of the chromatographic column.
[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. Expanding the protection scope of raw materials and templates: The method of this invention uses all mature and commonly used reagents from the laboratory or industrial production. The soft template covers cationic, nonionic, and anionic surfactants, while the hard template refines three types of silicon sources (alkoxysilanes, silica sols, and fumed silica), and is also compatible with phenol and resorcinol. With moderate polarity, all soft and hard templates can be stably assembled. Through a complete constraint combination of phenol or resorcinol + soft template + silane / silica sol series hard templates + fixed 1:1 alcohol-water solvent + constant temperature of 25~30℃ + ammonia water control before the ripening inflection point + bivariate synergistic linear particle size control, a wide range of particle sizes, high sphericity, and stable mesoporous structures can be simultaneously achieved.
[0024] 2. The method of the present invention does not change the solvent or the isothermal range throughout the process. Under the condition that other conditions remain unchanged, only the amount of template added and the amount of ammonia added are adjusted synchronously to achieve continuous linear control of the average particle size of resin microspheres in the range of 200 nm to 1000 nm. This overcomes the morphology and pore damage defects caused by the conventional industry operation of "changing solvent and adjusting temperature to change particle size" in the existing technology.
[0025] 3. The method of the present invention provides a fixed solvent and a standardized isothermal process, which only requires synchronous adjustment of two variables: template and ammonia. The particle size of 200~1000 nm is continuously controllable, and the process is stable and easy to scale up. Attached Figure Description
[0026] Figure 1 This is a high-magnification SEM image of the phenolic carbon spheres prepared in Example 1 of this invention (CTAB soft template, average 202 nm). The scale bar is 200 nm. The carbon spheres are perfectly spherical with fine wrinkled structures on the surface, uniform particle size, and no obvious melt adhesion.
[0027] Figure 2This is a SEM image of the phenolic carbon spheres prepared in Example 2 of this invention (CTAB soft template, average 505 nm). The particles within the field of view are highly uniform in size and do not adhere to each other, representing the preferred intermediate size sample of this invention.
[0028] Figure 3 This is a low-magnification panoramic SEM image of the phenolic carbon spheres prepared in Example 3 of this invention (CTAB soft template, average 986nm). Scale bar 500nm, magnification 20000x; under a large field of view, a large number of carbon spheres maintain an independent spherical shape, with only a few point contacts between particles, exhibiting excellent overall monodispersity.
[0029] Figure 4 This is a SEM image of the phenolic carbon spheres prepared in Example 8 of the present invention (TPOS silicon hard template, average 546 nm). The silicon hard template-phenolic co-assembly yields regular spheres, and after desilication, a broadened mesoporous structure can be obtained.
[0030] Figure 5 This is a SEM image of Comparative Example 1 of the present invention. Scale bar: 200 nm. This sample was prepared using an ethanol-water volume ratio of 1:4 with a high aqueous phase solvent. The micelle structure of the reaction system was destroyed, and the product consisted of a large number of random flocculent and fragmented agglomerates, which could not form independent and complete spherical carbon spheres.
[0031] Figure 6 This is a SEM image of Comparative Example 2 of this invention. Scale bar: 500 nm; the sample used was 6.0 vol% ammonia water (exceeding the upper limit of 3-5 vol% of this invention, resulting in particle size reversal). Numerous small particles fused together to form heterogeneous large aggregates with an extremely wide particle size distribution and no stable monodisperse particles. Detailed Implementation
[0032] It should be noted that the following embodiments are only used to illustrate the technical solution of the present invention and are not intended to limit the scope of protection of the present invention; conventional adjustments and substitutions of raw materials made by those skilled in the art based on the core process parameter range of the present invention all fall within the protection scope of the present invention.
[0033] All raw materials used in this invention are commercially available analytical grade reagents, and the testing instruments are standardized: SEM uses field emission scanning electron microscopy to observe particle size and morphology; nitrogen adsorption-desorption testing uses a 77K nitrogen adsorption instrument to calculate BET specific surface area and BJH pore size distribution; carbonization equipment is a tubular atmosphere furnace; centrifugation equipment is a high-speed benchtop centrifuge.
[0034] Standardized baseline reaction conditions (general fixed conditions for all examples and comparative examples): Mixed solvent: anhydrous ethanol and deionized water in a volume ratio of 1:1, with a total addition volume of 100 mL; The reaction constant temperature water bath temperature was 30 ℃. Phenolic molar ratio: Phenolic monomer: Formaldehyde in 37 wt% formaldehyde aqueous solution = 1:2.5; Polymerization stirring speed: 300 r / min, total stirring time at constant temperature: 24 h; Post-treatment washing: Wash with anhydrous ethanol and deionized water alternately by centrifugation 4 times, each time at 8000 r / min for 5 min; Drying conditions: 50 ℃ vacuum drying oven, heat preservation for 12 h; Standard carbonization process: nitrogen protection, gas flow rate 20 mL / min, heating rate 5 ℃ / min, constant temperature carbonization at 800 ℃ for 2 h, and natural cooling to room temperature.
[0035] Part 1: Examples of Soft Template Systems (CTAB / CTAC / F127 / PVP / SDS, In-situ Carbonization without Template) Example 1: CTAB soft template, target average particle size 200 nm (1) Solvent pre-temperature control: Measure 50 mL of anhydrous ethanol and 50 mL of deionized water (the volume ratio of anhydrous ethanol to deionized water is 1:1), mix them, place them in a constant temperature water bath, and keep the temperature stable at 30 ℃ for later use. (2) Template dissolution: Add 0.50 g CTAB (hexadecyltrimethylammonium bromide) to the constant-temperature mixed solvent and stir continuously for 30 min until completely transparent and free of white flocculent matter. At this point, CTAB accounts for 0.50 wt% of the total mass of the reaction solution. (3) Preparation of the catalytic system: Add 5.0 mL of 25 wt% concentrated ammonia to the above template solution, stir for 5 min to mix evenly, the ammonia accounting for 5.0 vol% of the volume fraction of the mixed solvent. (4) Phenolic polymerization feed: Weigh 1.1 g of resorcinol according to the phenol to aldehyde molar ratio of 1:2.5, dissolve it completely, add 2.0 g of 37 wt% formaldehyde aqueous solution, stir continuously at 300 r / min for 24 h to generate a light brown phenolic resin microsphere suspension. (5) Separation and drying: The suspension was centrifuged at 8000 r / min for 5 min, washed 4 times with anhydrous ethanol and deionized water, centrifuged at 8000 r / min for 5 min each time, and vacuum dried at 50 ℃ for 12 h to obtain brownish-yellow solid phenolic resin microsphere precursor powder. (6) Carbonization to remove template: The dry powder is placed in a quartz boat and pushed into a nitrogen tube furnace. Under nitrogen protection, the gas flow rate is 20 mL / min, the heating rate is 5 ℃ / min, and the carbonization is carried out at 800 ℃ for 2 h. The powder is then cooled to room temperature. CTAB is completely removed by in-situ thermal decomposition in a high-temperature inert atmosphere. After cooling, black mesoporous phenolic carbon ball powder is obtained.
[0036] Sample characterization test results: SEM observations as follows Figure 1 As shown, a large number of microspheres are uniformly dispersed, without adhesion or irregular particles, with a statistical average particle size of 202 nm; after carbonization, there is no obvious particle breakage, and the spheres remain intact.
[0037] Nitrogen adsorption test results: BET specific surface area 1485 m² / g, BJH average mesopore diameter 2.2 nm; Yield calculation: Theoretical solid content 112 mg, actual dried resin powder 82 mg, resin microsphere precursor powder yield 73%; Two CTAB soft templates were used to achieve a target average particle size of 500 nm. Step 15: The basic operation is the same as in Example 1, only the amount of CTAB and ammonia added is adjusted: The amount of CTAB added was 0.30 g (total solution 0.30 wt%), and the amount of ammonia added was 4.0 mL (solvent volume 4.0 vol%); the other solvents, temperature, feed amount, and carbonization parameters remained completely unchanged.
[0038] Sample characterization test results: SEM observation results as follows Figure 2 Monodisperse spherical particles with uniform particle size, no adhesion, no irregular particles, and an average particle size of 505 nm. These are representative samples of the intermediate standard size in this invention.
[0039] Nitrogen adsorption test: BET specific surface area 1178 m² / g, average mesopore diameter 2.6 nm; The yield of resin microsphere precursor powder was 80%. This embodiment represents the optimal process across the entire size range of the present invention, achieving the best balance between spherical and hole structures.
[0040] Implement 3 CTAB soft templates, with a target average particle size of 1000 nm. Steps 1-5 are performed in the same basic manner as in Example 1, with the following variable adjustments: CTAB 0.20 g (0.20 wt%), ammonia 3.0 mL (3.0 vol%); all other variables are fixed.
[0041] Sample characterization test results: SEM observations such asFigure 3 As shown: the large-sized microspheres have no particle fusion or deformation, with an average particle size of 986 nm; Nitrogen adsorption test: BET specific surface area 923 m² / g, average mesopore diameter 3.1 nm; The yield of resin microsphere precursor powder was 60%.
[0042] Example 4: CTAB soft template, replacing phenol monomer with phenol (low-cost route) The basic process is the same as in Implementation 2 (500 nm baseline ratio), except that 1.1 g of resorcinol is replaced with 0.94 g of phenol, the amount of formaldehyde remains the same, and all other conditions are completely identical.
[0043] Sample characterization test results: SEM observation: The particles are spherical and regular, with an average particle size of 410 nm. Nitrogen adsorption test: BET specific surface area 1190 m² / g, average pore size 2.5 nm; The yield of resin microsphere precursor powder was 78%.
[0044] Example 5: F127 Nonionic Soft Template The base solvent, temperature, phenol monomer (resorcinol), and ammonia water 4.0 vol% remain unchanged. CTAB is replaced with 0.32 g poloxamer F127 (0.32 wt% of total solution). The remaining polymerization, post-treatment, and carbonization steps are the same.
[0045] Sample characterization test results: SEM observation: Average particle size 460 nm; Nitrogen adsorption test: BET specific surface area 1220 m² / g, average pore size 2.8 nm. The yield of resin microsphere precursor powder resin was 76%.
[0046] Example 6: CTAC cationic soft template Same as the baseline parameters in Implementation 2, except that the template was replaced with 0.30 g cetyltrimethylammonium chloride (CTAC), and all other conditions remained unchanged; Sample characterization results: Average particle size 512 nm; BET specific surface area 1156 m² / g; average pore size 2.7 nm; sphericity similar to the CTAB system. Resin yield 79%.
[0047] Example 7: SDS anion exchange soft template composite (aiding in widening pore size) With the solvent and temperature unchanged, the template was prepared using a mixture of 0.25 g CTAB and 0.08 g SDS, and the system consisted of 4.0 vol% ammonia and resorcinol. Sample characterization results: SEM average particle size 445 nm, pore size distribution range broadened, BET specific surface area 1264 m² / g, average pore size 3.0 nm. The yield of resin microsphere precursor powder was 77%.
[0048] Part Two: Examples of Silicon-Based Hard Template Systems (TPOS / TEOS / TMOS / Silica Sol, Carbonization followed by Acid-Base Etching for Silicon Removal) Example 8 Hard template: Tetrapropoxysilane (TPOS) (1) 100 mL of 1:1 ethanol-water solvent at a constant temperature of 30 °C; (2) Hard template pre-hydrolysis: Add 0.35 g tetrapropoxysilane (TPOS) to water and stir at 30 °C for 20 min to complete the pre-hydrolysis, generating monodisperse nano-silica particles in situ. Then add ethanol at a volume ratio of 1:1 to water, with the silicon source accounting for 0.35 wt% of the total mass of ethanol-water solvent in step (1). (3) Add 4.0 mL of 25% ammonia water and stir evenly. Then add resorcinol and formaldehyde and polymerize at a constant temperature for 24 h. (4) The centrifugal washing and vacuum drying steps are consistent with the standard; (5) Carbonization: Standard 800 ℃ for 2 h; (6) Desiliconization etching: Carbon ball powder is placed in an 8 wt% NaOH aqueous solution, soaked at 80 ℃ for 4 h, washed with water multiple times until neutral, and dried to remove the silicon dioxide hard template.
[0049] Sample characterization test results: SEM characterization such as Figure 4 As shown: Silicon template self-assembles into regular spheres, and after desiliconization, ultra-large mesoporous carbon material is obtained with an average particle size of 546 nm. After desiliconization, the mesopores are greatly widened, with an average pore size of 4.9 nm for BJH, a specific surface area of 1490 m² / g for BET, and a resin precursor yield of 71%.
[0050] Implementation 9: Hard template: Tetraethyl orthosilicate (TEOS) The process is the same as in Implementation 8, except that TPOS is replaced with an equal mass of TEOS and pre-hydrolyzed for 20 min. Sample characterization test results: The carbon spheres have an average particle size of 532 nm, an average pore size of 4.7 nm, and a BET of 1465 m² / g. The resin yield is 70%.
[0051] Implementation of 10 rigid templates: nano-silica sol In a solvent isothermal system, 0.4 g of 30 nm alkaline silica sol (30% solid content) is added directly without pre-hydrolysis, and the remaining polymerization, carbonization, and hot alkaline etching steps remain unchanged. Sample characterization test results: The carbon spheres had an average particle size of 561 nm, a BET of 1432 m² / g, and an average pore size of 5.1 nm. The resin yield was 72%.
[0052] Part Three: Comparative Examples (Verifying one by one that the core limiting conditions of this invention cannot be omitted) Comparative Example 1: Solvent: Ethanol: Water = 1:4 (High aqueous phase, disrupts micelles) The remaining raw materials, temperature, CTAB 0.30 wt%, and ammonia 4.0 vol% were completely consistent with Implementation 2, only the solvent ratio of ethanol:water was adjusted to 1:4; Test results: As shown in Figure 5, SEM observation revealed no intact spherical microspheres after polymerization; the product consisted entirely of amorphous flocculent precipitates. After centrifugation, there were no irregular blocky solids, and the particle size could not be statistically determined. The nitrogen adsorption BET was only 426 m² / g, proving that fixing the 1:1 alcohol-water solvent is a necessary technical feature.
[0053] Comparative Example 2: Ammonia water volume 6.0 vol% (exceeding the upper limit of 3~5 vol% of this invention, resulting in particle size reversal) The rest is the same as in implementation 2, with the ammonia concentration increased to 6.0 vol%. Test results: SEM observations as follows Figure 6 As shown, a large number of small particles merge to form heterogeneous large aggregates with extremely wide particle size distribution, no stable monodisperse particles, and loss of linear control ability; a large number of channels are closed, and BET drops to 843 m², proving that ammonia water needs to be controlled within 5 vol%.
[0054] Comparative Example 3: The reaction was kept at a constant temperature of 40 ℃ (deviating from the 25~35 ℃ range). All other steps are the same as in Implementation 2, with polymerization performed at 40°C in a water bath; Test results: Particle collision and fusion intensified, and the average particle size increased to 720 nm; high temperature destroyed the ordered micelles of CTAB, the pore walls shrank and collapsed, the total pore volume decreased by 36%, and the BET was only 905 m² / g, proving that the isothermal range cannot be changed arbitrarily.
[0055] Comparative Example 4: High-ethanol system (ethanol:water = 8:1), using a TPOS hard template. The rest is the same as in implementation 8, except that the solvent is changed to ethanol:water = 8:1; Test results: RF (phenolic resin) prepolymer rapidly and randomly agglomerates, with a particle size range of 300~1400 nm. Spherical breakage is severe, and particles of different sizes are mixed, lacking narrow distribution characteristics.
[0056] Comparative Example 5: Polymerization of phenolic resin and ammonia without template addition. Solvent 1:1, 30 ℃, ammonia water 4 vol%, no soft / hard template; Test results: The product is a bulk cross-linked resin with no nanosphere structure and no mesopores. The BET is only 310 m² / g, proving that the template is a necessary condition for realizing porous nanospheres.
[0057] Part Four: Performance Summary Table of All Implementation Examples
[0058] Part Five: Comprehensive Results Analysis 1. Under a standardized system with a fixed ethanol / water ratio of 1:1, a constant temperature of 30 °C, and 3-5 vol% ammonia, this invention can stably obtain monodisperse phenolic microspheres with a particle size range of 200-1000 nm and a sphericity of ≥95% by synchronously adjusting the amount of template and ammonia added. 2. CTAB is the optimal cationic soft template, with the best linear control effect on particle size and regular pores; F127 and CTAC can be used as alternative industrial templates; silane-based TPOS / TEOS hard templates can significantly widen the pore size after etching, making them suitable for macromolecular adsorption scenarios; phenol can completely replace resorcinol to reduce raw material costs, with no significant deterioration in morphology and pore structure. 3. Three sets of key comparative examples respectively demonstrate that the solvent ratio, polymerization isothermal range, and upper limit of ammonia addition are all indispensable limiting technical features of this invention. If any one of them deviates from the range described in this invention, spherical breakage, particle size loss, and significant decrease in specific surface area will occur. 4. In-situ carbonization and removal of soft templates is a simple process; the mesopore size of silicon-based hard templates is significantly improved after etching with hot alkali or hydrofluoric acid, and the two routes can be flexibly selected according to the pore size requirements. 5. The yield of samples with a size of around 500 nm in the middle was the highest. The yield of samples with sizes of 200 nm and 1000 nm at both ends decreased due to centrifugal loss of small particles and slight cross-linking and breakage of large particles, but it was still significantly better than the extreme solvent (high or high ethanol system, corresponding to Comparative Example 1 and Comparative Example 4) system.
Claims
1. A room-temperature controllable preparation method for monodisperse mesoporous phenolic carbon spheres with a wide size range, characterized in that, Includes the following steps: Step 1: Dissolve or uniformly disperse the soft template in a mixed solvent of ethanol and water at a constant temperature of 25-35℃ with a volume ratio of 1:1, or add the silicon source hard template to water at a constant temperature of 25-35℃ for hydrolysis, then add ethanol at a volume ratio of 1:1 and maintain a constant temperature; then continue to add ammonia water catalyst with a mass concentration of 25-28 wt% and stir evenly, the volume of ammonia water accounting for 3.0-5.0 vol% of the volume of the mixed solvent of ethanol and water to obtain the reaction mixture; Step 2: Maintain a constant temperature and add phenol and formaldehyde aqueous solution to the obtained reaction mixture. The molar ratio of phenol to formaldehyde in the aqueous solution is 1:(2~3). Stir at a constant temperature for 18~24 h to carry out the polymerization reaction. The phenol is phenol and / or resorcinol, and the mass concentration of the formaldehyde aqueous solution is 37%. After the reaction is completed, the solid and liquid are separated, and the mixture is washed alternately with ethanol and water. Then, it is vacuum dried at 40~60℃ to obtain the resin precursor. Step 3: Perform template removal treatment on the obtained resin precursor: the soft template is decomposed by carbonization; the silicon source hard template is removed by acid etching or alkaline etching after carbonization. The carbonization method is as follows: under a nitrogen and / or argon atmosphere, the temperature is increased to 800℃ at a rate of 5℃ / min and held for 2 hours for carbonization, followed by cooling; The acid etching or alkaline etching method is as follows: After carbonization according to the above method, soak the desilication template in 5~10% hydrofluoric acid or NaOH aqueous solution of the total mass of carbonization; Step 4: When using a silicon-based hard template, after acid etching or alkaline etching, carbonize the material by heating it to 750–850 ℃ at a rate of 4–6 ℃ / min under an inert atmosphere of nitrogen or argon, holding it at that temperature for 1.5–2.5 h, and then cooling it to obtain mesoporous phenolic carbon spheres.
2. The method according to claim 1, characterized in that, The soft template in step 1 is selected from at least one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, poloxamer F127, polyvinylpyrrolidone, and sodium dodecyl sulfate.
3. The method according to claim 2, characterized in that, The anionic template sodium dodecyl sulfate is used in combination with the cationic soft template hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride, and the mass ratio of the combination of the anionic template sodium dodecyl sulfate to the cationic soft template hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride is 1:(3-4).
4. The method according to claim 3, characterized in that, The amount of the soft template added is 0.20~0.50 wt% of the mass of the ethanol and water mixed solvent in step 1.
5. The method according to claim 1, characterized in that, The hard template is selected from one of alkoxysilane, neutral nano silica sol, alkaline nano silica sol, and fumed silica; the alkoxysilane is selected from at least one of tetraethyl orthosilicate, tetrapropoxysilane, and tetramethoxysilane.
6. The method according to claim 6, characterized in that, The neutral and alkaline nano-silica sol is a 5~50 nm monodisperse SiO2 colloid.
7. The method according to claim 5, characterized in that, The amount of the hard template added is 0.15~0.60 wt% of the mass of the ethanol and water mixed solvent in step 1.
8. The method according to claim 5, characterized in that, Step 3, acid etching method, is as follows: soaking in hydrofluoric acid with a mass concentration of 10~20% for 6~24 hours; the acid etching method is as follows: soaking in NaOH aqueous solution with a mass concentration of 5~10% at a temperature of 60~90℃ for 3~6 hours.
9. The monodisperse mesoporous phenolic carbon spheres prepared by the method according to any one of claims 1 to 9, characterized in that, Its particle size is continuously adjustable from 200 to 1000 nm, and its sphericity is ≥95%. When using a soft template, the average pore size after carbonization is 2.2 to 3.1 nm. When using a silicon-based hard template, the average pore size after demolding is 4.5 to 5.2 nm. Its BET specific surface area is 600 to 1490 m² / g.
10. The application of the monodisperse mesoporous phenolic carbon balls of claim 9 in the fields of supercapacitor electrodes, industrial wastewater adsorption, multiphase catalytic supports, and gas separation chromatography packing materials.
Citation Information
Patent Citations
Phenolic resin-based spherical activated carbon as well as preparation method and application thereof
CN119683620A
